Soulager les douleurs de femmes lors de l’accouchement - Maud Arnal (Genre, Sexualité et Société)
In France, 80 % of women that are giving birth use epidural anesthesia. However, not everyone agrees on such medicalization of the childbirth-related pain’s alleviation. This article shows that the use of epidural anesthesia can be analyzed both as technical tool for the relief pain and a tool for behavioral social control of women during childbirth. Using an analysis of both observations and interviews conducted in a maternity ward, this article aims at highlighting how the relief of women’s pain during childbirth is driven by medical and social norms. Both the women themselves and the organization of healthcare work participate in enacting these norms. Such medical and social norms thus contribute to the production of a standardised emotional maternity revealing identity-related issues for the women and work-related issues for the midwives.